Predictive Modeling of Health Anxiety From Personality Dimensions and Physiological Stress Parameters - Nishimura, Ayako; Lin, Yu-Chen (Journal of Personality and Psychosomatic Research (JPPR), 2026)
The primary objective of this study was to develop a comprehensive predictive model of health anxiety by integrating foundational personality dimensions with objective physiological stress parameters. This cross-sectional study evaluated a sample of healthy adults in Taiwan. Psychological constructs were measured utilizing the Short Health Anxiety Inventory and the NEO Five-Factor Inventory. Objective physiological stress was quantified through baseline salivary cortisol assays and continuous heart rate variability monitoring to measure the root mean square of successive differences (RMSSD). Statistical evaluation was conducted using hierarchical multiple regression modeling to determine the incremental predictive validity of the physiological variables. The sample consisted of females with a mean age of . The final hierarchical regression model was highly significant and accounted for of the total variance in health anxiety. Trait neuroticism was the strongest psychological predictor ( ). Crucially, objective biological markers provided significant incremental predictive validity, with elevated baseline salivary cortisol ( ) and reduced parasympathetic vagal tone as measured by RMSSD ( ) serving as significant independent predictors of heightened health anxiety. Health anxiety is a profoundly psychophysiological condition driven by a synergistic interaction between inherent characterological vulnerabilities, such as neuroticism, and systemic autonomic and neuroendocrine dysregulation.